Serological and parasitological study and report of the first case of human babesiosis in Colombia (2003)
ABSTRACT: A study on the presence of Babesia in humans was performed in Puerto Berrío (Latitude 6.50deg. Longitude: -74.38deg. River: Magdalena. Area: 74.410km², Colombia-South America). Indirect immunofluorescence, thin and thick blood smears were used to study 194 individuals. Patients were grouped according to their risk-factors for Babesia infection: (group 1) individuals with fever, chills, sweating and other malaria-type symptoms (group 2) symptomatic and asymptomatic individuals from local cattle ranches, which were enrolled in an active form, and (group 3) workers from the local slaughterhouse. Seven individuals were serologically positive for Babesia: Three individuals presented IgM antibodies against B. bovis, while one had IgG against this species; one individual had IgM against B. bigemina, another had IgG and a third both IgM and IgG against this species. Only one individual was parasitologically positive for Babesiaand serologically positive for Babesia bovis (IgM 1:64)